2021
DOI: 10.5751/ace-01801-160111
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cue counting for estimating bird density using passive acoustic monitoring: recommendations for estimating a reliable cue rate

Abstract: Cue counting is a method developed for estimating vocally active wildlife density by dividing the density of cues (number of cues per unit area surveyed per unit time) by the average cue rate (ACR) at which individuals vocalize. It has been used successfully to estimate whale density using passive acoustic monitoring, but its efficacy has had limited testing in birds. We tested whether cue counting can be used to infer bird abundance using autonomous recording units and estimated the minimum effort required to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…We used bird vocalizations as a proxy for activity. This method has been validated by many other recent studies where bird vocal activity was found to be positively correlated with the abundance of birds (see a Review in Pérez- Granados & Traba 2021 and also Ducrettet et al, 2020; Pérez-Granados et al, 2021; Szymański et al, 2021). Using vocalizations to estimate activity is advantageous for many reasons as it allows collecting vast data over large spatio- temporal scales, but it also has its limitations.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…We used bird vocalizations as a proxy for activity. This method has been validated by many other recent studies where bird vocal activity was found to be positively correlated with the abundance of birds (see a Review in Pérez- Granados & Traba 2021 and also Ducrettet et al, 2020; Pérez-Granados et al, 2021; Szymański et al, 2021). Using vocalizations to estimate activity is advantageous for many reasons as it allows collecting vast data over large spatio- temporal scales, but it also has its limitations.…”
Section: Discussionmentioning
confidence: 83%
“…Acoustic monitoring has been on the rise as a useful method for assessing insect (Penone et al, 2013), bat (López - Bosch et al, 2022) and bird (Pérez -Granados et al, 2021) diversity. This methodology has several clear advantages: it is continuous and does not require the observer to be present and thus the animals are not affected by the measurement itself (Shonfield & Bayne 2017; Gibb et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Having the exact time of each call also allows extraction of average or maximum power (dB), which can be used for abundance or density estimation using distance‐sampling based methods (Sebastián‐González et al., 2018; Yip et al., 2020). Cue counting models are also useful ways to estimate density around recorders if a suitable estimate of the average cue rate is available for the target species (Pérez‐Granados et al., 2021). However, the sampling radius of an ARU is likely to be important, and obtaining reliable estimates of this is a key process for ARU use in ecological research (Pérez‐Granados & Traba, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Cue rates can vary with breeding status (Upham‐Mills et al., 2020), resource availability, and the presence of competitors and predators (Clay et al., 2012; Morales et al., 2014; Wheatcroft, 2015), and have been used to estimate absolute bird abundance in some methodological approaches (e.g. cue counting: Sebastián‐González et al., 2018; Pérez‐Granados et al., 2021; sonogram analysis: Drake et al., 2016).…”
Section: Introductionmentioning
confidence: 99%